Personal Reflections on the Masters in Educational Practice. (1st March 2017) - Jackson, Emma
In September 2015, I successfully completed the Masters in Educational Practice (MEP). This article focuses on the professional gains of this qualification including the opportunities for classroom-based inquiry, structured reflection and professional dialogue with colleagues. I discuss the benefits of mentoring support from experienced teachers, as well as ongoing professional development in key aspects of national educational policy and practice. I describe how the qualification encourages newly qualified teachers to continually reflect on their practice and how this has had a direct and long-lasting impact on my own practice and the practice of my MEP colleagues, enhancing the experience for pupils and raising standards in Welsh classrooms. Core to my own experience of the MEP was the encouragement of professional dialogue and networking with mentors, experienced teachers, academics and other newly qualified teachers. This community has formed a strong platform for generating, critically considering and sharing a wealth of ideas about excellent pedagogical practice. Within this article, I give practical examples of how my experiences of the MEP have directly benefitted the learners. I explain the relevance of the MEP modules and how these underpin the Welsh Government's three national priorities for improving educational outcomes for learners in Wales: improving literacy, improving numeracy and reducing the impact of deprivation on attainment. Therefore, I maintain that the qualification crucially demonstrates the interaction between classroom, local and national contexts. I hold that, without the MEP, I do not think that I would have developed as a practitioner as quickly or as effectively. The skill of critically reflecting on my practice is one which will benefit my learners for the rest of my teaching career.